2018
DOI: 10.1126/sciadv.aat2111
|View full text |Cite
|
Sign up to set email alerts
|

Cell chirality regulates intercellular junctions and endothelial permeability

Abstract: The handedness of the cell regulates the permeability of blood vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
86
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(96 citation statements)
references
References 50 publications
10
86
0
Order By: Relevance
“…We found that thalidomide, paroxetine, and methoxamine increased the percentage of counterclockwise (CCW) cells, suggesting a potential role of PKC in cardiac cell chirality (3134). Moreover, our work from the 2D micropatterning system with clockwise cells such as human umbilical vein endothelial cell (HUVEC) lines (27) demonstrated that the activation of PKC signaling reverses chirality of endothelial cells from clockwise (CW) to CCW (35). Based on these results we identified PKC signaling as a promising candidate for regulating the chirality of cardiac cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that thalidomide, paroxetine, and methoxamine increased the percentage of counterclockwise (CCW) cells, suggesting a potential role of PKC in cardiac cell chirality (3134). Moreover, our work from the 2D micropatterning system with clockwise cells such as human umbilical vein endothelial cell (HUVEC) lines (27) demonstrated that the activation of PKC signaling reverses chirality of endothelial cells from clockwise (CW) to CCW (35). Based on these results we identified PKC signaling as a promising candidate for regulating the chirality of cardiac cells.…”
Section: Resultsmentioning
confidence: 99%
“…One of the key findings of this study is that PKC activation reverses the handedness of cardiac looping and correspondingly the chirality of the cardiac cells. This is supported by the fact that PKC activators such as TPA and Indolactam V switch the chirality of endothelial cells from CW to CCW (35). One of the promising PKC isoform candidates is PKC-α which mediates the switch of cell chirality in endothelial cells.…”
Section: Discussionmentioning
confidence: 97%
“…The re‐positioning of tight junction proteins and proton pumps alters host cell absorption of ions and contributes to EPEC‐associated diarrhoea (Tapia, Kralicek, & Hecht, ). Furthermore, the importance of cell chirality, or cell asymmetry in the left‐to‐right axis, to endothelial permeability has also been recently demonstrated with regard to altered tight junction integrity during enteric infection (Fan et al, ). This is a novel finding as cell chirality was previously only associated with embryonic development (L. Q. Wan et al, ).…”
Section: The Physical Landscape and Ae Pathogensmentioning
confidence: 99%
“…[ 106 ] Rotational changes in stretch direction can induce reorientation of ECs to new axes, actin cytoskeletal reorganization, and changes in morphology. [ 107,108 ] Similar to shear stress, physiological CS (5–10%) helps maintain fundamental processes including angiogenic sprouting, matrix remodeling via MMP secretion, growth factor and vasomodulatory secretion, and protection from apoptosis via stretch‐activated ion channel stimulation, integrin engagement, and downstream mechanotransductive signaling. [ 42,109,110 ] However, pathological CS (>20%), caused by hypertension, can result in enhanced ROS and TNF‐α production, increased apoptosis, and imbalanced MMP secretion, ultimately affecting EC patency and permeability.…”
Section: Vascular Hemodynamics and Mechanotransductionmentioning
confidence: 99%